BORN INTO THE TROUBLES: DEIRDRE MADDEN’S HIDDEN SYMPTOMS - Tamara, Benito de la Iglesia (International Journal of English Studies, 2002)
The purpose of this study is to examine Deirdre Madden’s Hidden Symptoms (1986) analysing how, in a city affected by the Northern Irish strife, attitudes towards the conflict seern rnostly motivated by the personal connection of the characters with it. Thus, although the main protagonists have all been born into the troubles and are suffering the effects of thern, they have -if any- distinct political positions and religious tendencies and they cope with the situation in different ways. throughout this article I will explore, along with other aspects, the insecurity in people’s lives, violence, and religion as oppressive forces.